واقع هيئة الرقابة الشرعية في البنك الإسلامي الأفغاني: دراسة مقارنة مع التجربة الماليزية: The Challenges of Institutional Ijtihad in Islamic Finance: Causes and Potential Solutions - Athari, Zaif Ullah; Muhammad Amanullah; Bouhedda Ghalia (International Journal of Al-Turath In Islamic Wealth and Finance, 2024)
الملخص يهدف هذ البحث إلى دراسة واقع هيئة الرقابة الشرعية في البنك الإسلامي الأفغاني: دراسة مقارنة مع التجربة الماليزية. لقد تعتبر أداة واقع الرقابة الشرعية صيغة فقهية وصبغة اقتصادية وصياغة مصرفية جديدة. فالبنك الإسلامي الأفغاني يتضمن هيئة الرقابة الشرعية التي تراجع وتقيم العمليات المالية والمنتجات المصرفية لضمان توافقها مع الشريعة الإسلامية. تم التركيز في هذا البحث على بيان تعريف الرقابة الشرعية لغة واصطلاحًا، مع المقارنة التقويمية بين هيئة الرقابة الشرعية في البنك الإسلامي الأفغاني وهيئات الرقابة الشرعية في بنك إسلام الماليزي وبعض المصارف الإسلامية الماليزية الأخرى. وقد ذكر الباحثون في هذه الدراسة النقاط المشتركة والنقاط المختلفة بين التجربتين. لقد اتبع الباحثون في هذا البحث المنهج الاستقرائي، والمنهج التحليلي النقدي لدراسة آراء العلماء في الموضوع ومناقشتها. كما اعتمدوا على الدراسة الميدانية، وذلك عن طريق المقابلة الشخصية مع المتخصصين في هذا المجال. توصل هذا البحث إلى نتائج، منها: يظهر أنّ هيئة الرقابة الشرعية في البنك الإسلامي الأفغاني ليس لها نظام رقابي قوي يتماشى مع التطورات العالمية المعاصرة؛ لكي يؤدي إلى تنظيم وإنجاح الاجتماعات واتخاذ القرارات بإطار قانوني متطور؛ وذلك لدعم فاعلية البنك ويعزز مصداقيته؛ كما أنه لا توجد هناك التشريعات القانونية التي تدعم الهيئة الشرعية؛ ويوجد تفاوت فاحش بين الهيئات الشرعية في البنك الإسلامي الأفغاني والمصارف الإسلامية الماليزية، وذلك من حيث الإلمام بمعرفة اللغات العلمية من العربية والإنجليزية، وعدد الاجتماعات الدورية، وكيفية تعيين الأعضاء، ومن حيث قدم التجربة وحداثتها. إضافة إلى ذلك، هناك تشابه في تخصصات أعضاء الهيئتين وأداء مهامها، حيث تشكل الهيئة الشرعية في كلتي التجربتين من علماء الشريعة الإسلامية. ومن أهم التوصيات التي توصل إليها هذا البحث هي: ضرورة إنشاء علاقات وثيقة بين البنك الإسلامي الأفغاني والمصارف الإسلامية الماليزية حتى يتمكن البنك الإسلامي الأفغاني من تبادل المعرفة والاستفادة من خبراتها في مجال الرقابة الشرعية. الكلمات المفتاحية: واقع الرقابة الشرعية، المقارنة التقويمية، البنك الإسلامي الأفغاني، التجربة الماليزية. Abstract This research aims to examine the status quo of Shariah supervisory boards in the Afghan Islamic Bank: A comparative study with the Malaysian experience. Shariah supervisory oversight is considered a juristic formulation, an economic complexion, and a new banking framework. The Afghan Islamic Bank incorporates a Shariah supervisory board that reviews and evaluates financial operations and banking products to ensure compliance with Islamic law. This research focused on elucidating the definition of Sharia Supervision in both linguistic and technical terms, with a comparative evaluation between the Sharia supervisory Board of the Afghan Islamic Bank and the Sharia Supervisory Board of the Islamic Bank of Malaysia and some other Malaysian Islamic banks. Researchers in this study have outlined commonalities and differences between the two experiences. The researchers employed an inductive approach and analytical-critical method to study scholars’ opinions on the subject and discuss them. Additionally, they relied on field research, conducted through personal interviews with specialists in the field. This research concludes several findings, including: the absence of a robust regulatory system for Shariah supervisory boards in the Afghan Islamic Bank that aligns with contemporary global developments, to facilitate the regulation and success of meetings and decision-making within a sophisticated legal framework, thus supporting the bank’s effectiveness and enhancing its credibility. Moreover, there is a lack of legal legislation supporting the Shariah board, and there is a significant disparity between Shariah boards in the Afghan Islamic Bank and Malaysian Islamic banks regarding familiarity with scientific languages such as Arabic and English, the frequency of meetings, member appointment procedures, and the maturity of the experience. Furthermore, there are similarities in the specializations of board members and their performance tasks, as Shariah boards in both experiences consist of Islamic jurisprudence scholars. One of the most important recommendations reached by this research is the necessity of establishing strong relationship between the Afghan Islamic Bank and Malaysian Islamic Bank. This would enable the Afghan Islamic Bank to exchange knowledge and benefit from their expertise in the field of Sharia supervision. Keywords: Shariah supervision reality, comparative evaluation, Afghan Islamic Bank, Malaysian experience.